Characteristics of Hormogonia Formation by Symbiotic Nostoc spp. in Response to the Presence of Anthoceros punctatus or Its Extracellular Products - Campbell, Elsie Lin (1989)
Nostocacean cyanobacteria typically produce gliding filaments termed hormogonia at a low frequency as part of their life cycle. We report here that all Nostoc spp. competent in establishing a symbiotic association with the hornwort Anthoceros punctatus formed hormogonial filaments at a high frequency in the presence of A. punctatus. The hormogonia-inducing activity was produced by A. punctatus under nitrogen-limited culture conditions. The hormogonia of the symbiotically competent Nostoc spp. were characterized as motile (gliding) filaments lacking heterocysts and with distinctly smaller cells than those of vegetative filaments; the small cells resulted from a continuation of cell division uncoupled from biomass increase. An essentially complete conversion of vegetative filaments to hormogonia occurred within 12 h of exposure of Nostoc sp. strain 7801 to A. punctatus growth-conditioned medium. Hormogonia formation was accompanied by loss of nitrogen fixation (acetylene reduction) and by decreases in photosynthetic CO(2) fixation and in vivo NH(4)(+) assimilation of 30% and approximately 40%, respectively. The rates of acetylene reduction and CO(2) fixation returned to approximately the control rates within 72 to 96 h after hormogonia induction, as the cultures of Nostoc sp. strain 7801 differentiated heterocysts and reverted to the vegetative growth state. The relationship between hormogonia formation and symbiotic competence is discussed.